Minha atuação como diretora escolar na perspectiva de gestão colaborativa: estratégias em um CEI da rede parceira do município de São Paulo - Theodossiou, Roberta de Freitas (2023)
This research focuses on the role of a school director in an Early Childhood Education Center of the Municipal Partner Network of São Paulo. The guiding question of this research is: How can a perspective of collaborative management be introduced and maintained in the school routine to enable a practice of director's role based on collaborative work, and what are the possible paths considering that the director needs to organize their management based on the set of regulations and procedures resulting from the public policy system of São Paulo, institutional guidelines, and the challenges of the unit's reality, which must provide care considering the uniqueness of infants, children, and their families? The general objective is to analyze the role of the school manager from the perspective of collaborative management. The specific objectives are: to identify the laws and institutional guidelines that guide the pedagogical practices of the school director in Early Childhood Education in the partner network, to investigate the paths that the school management seeks to meet the demands of daily life, to analyze the role of school management from the perspective of collaborative management with the educational community, and to verify the possible paths for the implementation of collaborative management practices. We assume that, even in the face of complexity and challenges in the school administration of Early Childhood Education Centers in the partner network of São Paulo, there are ways for a management that enables collaborative work with the participation of the educational community in everyday processes. The research participants include a school director, two pedagogical coordinators, two teachers, a school supervisor, a representative from a Civil Society Organization (CSO), and a mother of a child enrolled in the Early Childhood Education Center, representing the Community Education Council. The methodological approach used is qualitative research. The data collection instruments include documentary research, bibliographic analysis, and focus groups. The theoretical framework is based on authors who address collaborative culture in schools and management and leadership by Jorge Ávila de Lima, Heloísa Luck, Michael Fullan, and Andy Hargreaves. The research results indicated that even though the educational system hinders processes for the effectiveness of the autonomy of the educational community in school decision-making, the role of the school director from the perspective of collaborative management can be a possible path towards the construction of a more democratic and humane school environment, and that various strategies and daily actions can foster collaborative practices within the Educational Unit and enable a path of educational resignification.